Severity of dental fluorosis among 12-15 years old school children in Zeway, Oromia Region, Ethiopia - Gebretsadik, Heron Gezahegn (Orapuh Journal, 2021)
IntroductionFluorine is the most electronegative of all chemical elements and is largely found in the chemically combined state of fluoride. Fluoride at an optimum level does not only decrease the incidence of dental caries but also maintains the integrity of oral tissues. While fluoride is accepted as being effective in the prevention of caries, the excessive consumption of fluoride can put bones and teeth at risk of developing fluorosis. Dental fluorosis is a condition affecting teeth and is caused by an increased intake of fluoride over an extended period during tooth development (until the age of six). Clinically it is characterized by hypo-mineralization with opaqueness and brownish discoloration (staining) of tooth surfaces. The degree of hypo-mineralization and staining disclose the severity of the condition. PurposeThe purpose of this study was to assess the severity of dental fluorosis among 12-15 years old school children in Zeway, Oromia Region, Ethiopia.Materials and MethodsA descriptive cross-sectional study was conducted between June 5 and July 9, 2018. A total of 1290 school children participated in the study. The severity of dental fluorosis was assessed using Dean`s Dental Fluorosis Index. A questionnaire, which incorporates Dean’s fluorosis index was used as a data collection instrument. Careful oral examination was carried out by the calibrated researcher (clinician).ResultOut of the total 907 study participants with the condition, 30.7% (n=278) had severe dental fluorosis followed by 31.2% (n=283) moderate, 33.8% (308) mild, 2.5% (n=23) very mild, and 1.8% (n=17) questionable. In other words, of those who had the condition, 95.7% of study participants showed mild to severe dental fluorosis. 60.7% of males and 62.9% of females manifested a moderate or severe form of dental fluorosis There was no significant gender variation of severity among the participants. ConclusionMajority of the participants manifested mild to severe dental fluorosis. The results of this study suggest the necessity for immediate water defluorination and the creation of oral health awareness in the study area concerning dental fluorosis.